2012
DOI: 10.1016/j.jtcvs.2012.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac catheterization within 1 to 3 days of proximal aortic surgery is not associated with increased postoperative acute kidney injury

Abstract: Objective Cardiac catheterization shortly before coronary artery bypass grafting or valve surgery has been associated with increased postoperative acute kidney injury. The relationship between catheterization timing and acute kidney injury following proximal aortic surgery remains unknown. Methods Between August 2005 and February 2011, 285 consecutive patients underwent cardiac catheterization prior to elective proximal aortic surgery with cardiopulmonary bypass at a single institution. The association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
3
10
1
Order By: Relevance
“…We did not find that a shorter preoperative cardiac catheterization interval (≤5 days) is associated with a higher AKI incidence in isolated SAVR. These results reiterate the conclusions of other research groups who found that delaying isolated valve surgeries after coronary angiography is not justified in most patients . Whenever AKI occurs, efforts should focus on providing an early diagnosis and treatment plan, especially that duration of AKI has been shown to impact long‐term survival following cardiac surgery .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We did not find that a shorter preoperative cardiac catheterization interval (≤5 days) is associated with a higher AKI incidence in isolated SAVR. These results reiterate the conclusions of other research groups who found that delaying isolated valve surgeries after coronary angiography is not justified in most patients . Whenever AKI occurs, efforts should focus on providing an early diagnosis and treatment plan, especially that duration of AKI has been shown to impact long‐term survival following cardiac surgery .…”
Section: Discussionsupporting
confidence: 74%
“…These results reiterate the conclusions of other research groups who found that delaying isolated valve surgeries after coronary angiography is not justified in most patients. [30][31][32] Whenever AKI occurs, efforts should focus on providing an early diagnosis and treatment plan, especially that duration of AKI has been shown to impact long-term survival following cardiac surgery. 10 Some major therapeutic principles are: 1) maintenance of systemic hemodynamics through the detection and treatment of volume depletion, improvement of cardiac contractility using inotropes, and reduction of afterload with vasodilators, 2) avoidance of nephrotoxic drugs and agents, 3) use of diuretics such as furosemide 29,30 to increase urine output, 4) mesenchymal stem cells (MSC), a novel and promising therapeutic option whose benefits are related to the release by MSCs of factors promoting tubular cell proliferation, [33][34][35] and if all fails to improve renal function, 5) early renal replacement therapy can be attempted, as it has shown promising results in some series.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of association between CAG on preoperative days 1 through 3 and increased risk of AKI in the one study of the CPB/DHCA subgroup seems controversial, given that the pooled effect of the CPB subgroup did show a significant association (adjusted OR, 0.35; 95% CI, 0.17-0.73; P  = 0.005) [10]. However, the CPB/DHCA subgroup had a much more higher incidence of AKI, about 31% if defined by the RIFLE criteria, while, the highest incidence of the other studies was only 18% if defined by the RIFLE criteria, or 32% if defined by the AKI network criteria [9].…”
Section: Discussionmentioning
confidence: 99%
“…The Duke Thoracic Aortic Surgery Database is a prospectively maintained electronic clinical registry of all patients who have undergone thoracic aortic surgery at Duke University Medical Center (Durham, NC) since 2005. 21, 22 A query of the database identified 387 consecutive TEVAR operations performed between March 2005 and January 2012; of these, 87 (22%) were hybrid arch repairs and form the basis of this report. General criteria regarding patient selection for hybrid arch repair are listed in Figure 1.…”
Section: Methodsmentioning
confidence: 99%